Strategy Development Business Of Gapoktan Sari Agung In Sedahan Jaya Village At District Sukadana - Hery Medianto Kurniwan; Isfian Dwi Nugroho (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2020)
The aim is to develop a strategy for developing a business development strategy for Gapoktan Sari Agung in Sedahan Jaya Village, Sukadana District. The data analysis used in this research is qualitative analysis, which explains the marketing strategy using SWOT analysis, namely by looking at the internal environment in the form of Strength and Weakness and the external environment in the form of Opportunity and Threat. The combination of internal and external factors is seen through the Quadrant Analysis of the TOWS Matrix comparing internal factors (Strength and Weakness) and external factors (Opportunity and Threat). The results showed the main strength of the Sari Agung Gapoktan members were all members of Gapoktan Sari Agung who worked on rice farming with a score of 0.022, while the main weakness factor of Sari Agung was that the rice production produced by the Sari Agung Gapoktan members was not continuous with a score of 0.021. . The main opportunity for Gapoktan Sari Agung is the demand for local (village) rice which tends to increase with a score of 0.026, while the main threat factor for Gapoktan Sari Agung is changes in people's tastes and purchasing power with a value of 0.022. Based on the Total Score Score of strengths, weaknesses, opportunities and threats are at S = 0.022, W = 0.021, O = 0.026 and T = 0.022. From this data, the quadrant coordinate point is obtained which is at (S - W) = (0.022 - 0.021) = 0.001, (O - T) = (0.026 - 0.022) = 0, 004 to be precise in Kudaran I with the coordinate point (0.001: 0.022). From the marketing strategy map, Gapokatan Sari Agung in Sedahan Jaya Village is in Quadrant I. Quadrant I provides an overview regarding a very favorable situation because the Sari Agung Farmers Group Association (GPOKTAN) in Sedahan Jaya Village, Sukadana District has positive strengths and opportunities. so that they can take advantage of existing opportunities. The strategy that must be implemented is to support an aggressive growth policy (Growth Oriented Strategy). Keywords : Stregey Development, Business, SWOT